DAMPAK PERANG RUSIA-UKRAINA TERHADAP PEREKONOMIAN GLOBAL - Johnson Kennedy, Posma Sariguna (Universitas Kristen Indonesia, 2023)
Geopolitical events, such as the Russia-Ukraine conflict, have a significant impact on global commodity, financial, and capital markets. This conflict creates uncertainty that can influence investor sentiment, stock prices, trade activities, and the broader economy. The study employs a qualitative approach to examine the impact of the Russia-Ukraine conflict on the global economy. The research findings reveal an increase in global commodity prices, financial market fluctuations, and capital market volatility, with varying effects across different sectors. Additionally, the conflict affects the Indonesian economy, particularly concerning oil imports and the exchange rate of the rupiah. With the growing geopolitical uncertainty, a better understanding of its impact becomes crucial for making informed decisions in the global market. This research provides value in identifying risks and opportunities and assists stakeholders in making sound decisions amid emerging geopolitical risks.Keywords: Russia-Ukraine War, Global Economy, Geopolitical Ris